Theoretical Calculations of the Electron Transport Parameters in CH4-Ar and CH4-Ne Mixtures Gases Using Monte Carlo Method - Jawad, Enas Ahmed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The result of concentration varying of mixture methane with argon and neon gas are believed to study the change in electrons energy distribution function and then the change of the electrons transport parameters including the drift velocity, the mean energy, characteristics energy and diffusion coefficient. In the present work,a contemporary developed computer, simulation program known as Bolsig+ is being used for calculating the electron transport parameters.